THE INFLUENCE OF BUDGET SYSTEM ACCOUNTABILITY AND ACCOUNTANCY PROFESIONAL TO EVALUATION OF BUDGET GOVERNANCE - Dewi, Kurnia Sari (International Journal of Artificial Intelligence Research, 2025)
In the rapidly changing uncertain and dynamic environment characterized by limited resources, the global economic crisis imposed a new attitude to budgetary control and made it one of the leading functions of management. The management function "control" invariably includes evaluation as an element of feedback. In this regard, a number of authors consider the procedure for evaluating the implementation of budgets by the centers of responsibilities in the budget control process. The purpose of this publication is to identify some basic problems in enterprise valuation related to budgetary control, which are known in the Indonesian  scientific literature. The article reviews the Indonesian  scientific literature indexed in the Google Scholar scientific database until the end of July 2023. The study was conducted in three stages, including developing the search protocol, conducting the search, and reporting the results. Methodologically, a systematic approach was applied, based on eleven scientific publications in Bulgarian, which correspond to the research problem under study. As a result of the review, problems were identified in the assessment of the enterprise's budgetary control process. Some authors bring to the fore as a problem the ineffective internal control in business organizations, presupposed by the lack of a good level of availability of information. To solve it, a modern toolkit is applied, which enables the evaluation and successful management of internal risk. In the conditions of the global economic crisis, the authors most often recommend the concepts and approaches of "assessing achievements in budgetary control", BSC(Balanced Scorecards) and controlling as particularly attractive and successful. These concepts and approaches imply qualitatively new requirements for the necessary information. Another major estimation problem in the budgetary control process is accounting for the interrelationships between variances. Also, most authors do not discuss the managerial issues related to the methodology for evaluating responsibility centers. In the conclusion, recommendations for future research on the topic are given. In the opinion of the author, the results of this scientific development can be useful for making informed decisions in the field of internal control. Despite the theoretical nature of the study, it can be used by both researchers and management practice